The Analysis of Adversity Quotient on Problem Solving Skills of Students Guidance and Counseling Faculty of Education and Teacher Training Sriwijaya University - Risma Anita Puriani; Dewi, Ratna Sari; Mimhamimdala, Fuad; Yanti, Prima (Kuras Institute, 2021)
This research is based on the development of students notalways running smoothly, in the development, students experiencing obstacles and difficulty. The purpose of the research is to produce and analyze the data of adversity quotient and problem solving skill and see the effect of adversity quotient on problem solving skill of Guidance and Counseling Students, Sriwijaya University. This type of research is quantitative research using survey methods as well as data analysis techniques using regression analysis. The sample in this study of 142 students consisted of three generations of 2017, 2018 and 2019 Guidance and Counseling Study Program, Faculty of Teacher Training and Education Sriwijaya University. Sampling techniques using Proportional Random Sampling. The instruments in this study used likert scale which has been tested validity and reliaitscredibility. The conclution is that there is an influence adversity quotient on problem solving skill of Faculty of Teacher Training and Education students of Sriwijaya University, its mean the higher adversity quotient of students in then the higher the problem solving skill owned by students of Guidance and Counseling Study Program, Faculty of Teacher Training and Education, Sriwijaya University. The implications of this research are used as input in the creation of guidance and counseling service programs.